An adjoint based gradient optimization chain for complex helicopter fuselage parts using a free form deformation or CAD based parameterization method - Wentrup, M. (My University, 2015)
In this paper a gradient based optimization chain for aerodynamic shape optimization is described. The chain includes the DLR TAU-code for flow evaluations, while a discrete adjoint approach is used to compute the gradient of a high count of design variables. For parameterization of complex helicopter fuselage parts, two different methods were implemented. The first method uses the Free Form Deformation technique to modify the shape by manipulating the control points of a NURBS-volume. The second approach is to use the CAD software CATIA V5 to build up a parametrical model for optimization. To investigate both methods with different settings, the ROBIN-mod7 fuselage was chosen to reduce drag by optimizing the relative simple back door geometry. After gaining experience with this example, the optimization chain is used to optimize the shape of the common helicopter platform sponsons in the scope of the European Clean Sky GRC2-project. It could be shown that for both examples a reduction of the drag force was achieved (drag reduction of 21.76% for the ROBIN-mod7 test case and 1.49% drag reduction for the sponsons optimization).
Keywords: Green Rotorcraft